DIMENSI EDUKATIF KISAH NABI IBRAHIM DALAM AL-QUR’ĀN - Arif Budiono (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
The article explain about the educative dimension in the story of Prophet Ibrahim. Where al Qur’an has told a lot of events that can be taken and learned in life today, the prophet narrated by the Qur'an is the story of Prophet Ibrahim As. whose names are often referred to up to 69 times, even one of the letters is named Surah Ibrahim. Prophet Ibrahim succeeded in forming the personalities of his sons and his wives obeyed God and had high social piety. Fidelity of Prophet Ismail and Prophet Ishaq, Siti Sarah and Siti Hajar's steadfastness and patience became authentic proof of his success in instilling values and characters that reflect true Muslims. The value of character education that has been taught by Prophet Ibrahim to his family and people has become very relevant to be applied in the world of education, amid the nation's moral condition which is very worrying nowadays.Keywords: Educative Dimension, Story, and Ibrahim